2021
DOI: 10.1155/2021/9309904
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology and Studies on Transport Behavior: A Literature Analysis, Integrated Research Model, and Future Research Agenda

Abstract: The prevalence of mobile technology has been significant in transport research. Despite a growing application spectrum of smartphone uses and interests in mobility inference, little effort has been put into discussing theories, models, and research topics based on a systematic study of scholarly sources rooted in the interdisciplinary area of mobile technology and transport. Therefore, a timely and comprehensive synthesis of the current state of research is deemed to be required. A literature analysis, followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 254 publications
0
2
0
Order By: Relevance
“…In today's quickly expanding educational scene, the incorporation of technology has become a key aspect in molding the future of higher education [26]. Big data analytics and mobile-driven processes are seen as significant drivers of innovation and informed decision-making within the realm of disruptive technology [27]. In this study, we have engaged in a thorough examination of the study aim and a collection of relevant research inquiries related to the topic of "Empowering Higher Education: A Big Data Analytics Approach to Mobile-Driven Decision-Making."…”
Section: Conclusion and Future Agendamentioning
confidence: 99%
“…In today's quickly expanding educational scene, the incorporation of technology has become a key aspect in molding the future of higher education [26]. Big data analytics and mobile-driven processes are seen as significant drivers of innovation and informed decision-making within the realm of disruptive technology [27]. In this study, we have engaged in a thorough examination of the study aim and a collection of relevant research inquiries related to the topic of "Empowering Higher Education: A Big Data Analytics Approach to Mobile-Driven Decision-Making."…”
Section: Conclusion and Future Agendamentioning
confidence: 99%
“…Behavioral intention to use travel apps is a subject of study for accommodation reservations and other types of reservations-airline tickets, car rental, and cruise reservations [55], visits to national parks [56], restaurants reservations [55,56], natural habitats tours [29]. Research concerns on the use of mobile applications for urban tourism we also found in articles addressing the use of mobile applications for local transport [57][58][59][60][61][62][63][64][65]. Tour guide apps assist travelers while waiting in airports [66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to this situation, the awareness of journey planning and learning about waiting time, commuting time, numbers of transfers, trip distance, and cost has disintegrated among urban rail passengers. It could also be because there is a lack of clear frameworks of data gathered through mobile technology users that work for transport sectors (Sun et al, 2021). Previous studies concerning mobile app adaptation in different contexts can affect mobile app users' behaviour (Matyas, 2020;Siuhi & Mwakalonge, 2016).…”
Section: Introductionmentioning
confidence: 99%